Humus and Humic Substances Recent Advances - Makan, Abdelhadi (IntechOpen, 2022)
Besides live biomass and decaying dead biological matter, humus constitutes an important component of organic matter in the soil. Humic substances are heterogeneous polymers formed during the process of decay and degradation of plant, animal, and microbial biomass. The humic fraction of organic matter is a stable nutrient base that serves as a slow-release source of carbon and energy for indigenous, slow-growing microorganisms in the soil. This book discusses recent advances and applications of humus and humic substances in agriculture, industry, and the environment. Chapters address such topics as the chlorination and phenanthrene sorption for humic and fulvic acids extracted from different soils, humic substances as growth promoters for farm animals, dynamics and function of humus from tropical forests, and much more.